Copolymer and platinum ion assisted growth of functionalized gold nanonests - Yang, Jing-Cyuan; Chang, Yi-Hsiang; Whang, Wha-Tzong; Chen, Chun-Hua; Wu, Ren-Jye (My University, 2015)
This paper describes a facile low-toxicity synthesis of two different types of Au nanonests and one binary Au-Pt core-shell nanonest with high yield and excellent uniformity in size and morphology using block copolymer P123 (EO20PO70EO20) as a soft template and the main reductant in an ice water bath. The introduction of a suitable second metallic source, i.e. Pt ions in the present case, was proven to be a unique strategy for effectively governing the reduction sites of P123 for Au nucleation, which leads to significant changes especially in the crystallite size of the grown Au nanonests. The Au nanonests exhibited a distinct morphology-dependent surface plasmon resonance (SPR) that is red-shifted by similar to 140 nm from the spherical particles wavelength, and significant surface-enhanced Raman scattering (SERS), allowing the rapid determination of rare malachite green oxalate (MGO).